PUBLIC INTEREST PROTECTION PROBLEM IN THE SPATIAL PLANNING PROCESS - Lastauskienė, Giedrė; Bakšienė, Daiva (Teisė, 2015)
The Law on Spatial Planning that entered into force in 2014 is named a revolutionary measure that ought to radically change the regulation common for this field, and that, supposedly, has eliminated most of the problems that existed in this field. After analysing the law and more than one year of experience of its implementation, one may conclude that the regulatory change was highly favourable for business representatives and provided them with more opportunities to start construction operations faster and easier than it used to be. The article notes that without defining certain categories in the law, the concepts expressing constitutional values such as the healthy environment, it’s protection, human health and others, are interpreted in a narrower scale, potentially favourable to a certain group of interests, meanwhile, providing such conditions means inadequate regulatory trends. It should be noted that the text of the law was formulated using such language structures based on which the relevant public needs are taken into account only if the violation of a particular legal norm (as opposed to the principle or value) is proven. It can be reasonably assumed that the new legal regulation has limited the representation of public interests and possibilities of the public to really participate in spatial planning processes, and this situation is not consistent with the principle of sustainable development of territories, the constitutional doctrine of human rights and the provisions of Aarhus Convention. The transposition of large part of spatial planning processes to the regulation sphere of the Law on Public Administration significantly limited the possibilities of self-government to make creative and rational decisions that are most consistent with local expectations. There is a suspicion that certain provisions of the laws which severely limit the implementation of the discretionary functions of the local municipality – spatial planning – are possibly unconstitutional. It is noted that a change in the nature of regulation and the introduction of a general rule that, in many cases, the construction can be carried out without a detailed plan, did not provide sufficient safeguards to ensure sustainable and rational development of territories and really listen to the needs and expectations of the concerned public.